1985
DOI: 10.1093/ajcn/42.2.242
|View full text |Cite
|
Sign up to set email alerts
|

Indices of copper status in humans consuming a typical American diet containing either fructose or starch

Abstract: Twenty-four male subjects originally participated in a study to determine the effects of feeding diets comparatively low in copper (1.03 mg/day/2850 kcal) and containing either 20% fructose or starch on indices of copper status. During the course of feeding the diets for 11 wk, four of the subjects exhibited heart-related abnormalities and were removed from the study. Fructose ingestion had no effect on serum ceruloplasmin activity or serum copper concentration but did significantly reduce cuprozinc superoxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0
1

Year Published

1987
1987
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(79 citation statements)
references
References 35 publications
5
73
0
1
Order By: Relevance
“…For example, we have recently shown in another double-blind, placebo-controlled crossover trial that Cu supplementation with 3 or 6 mg elemental Cuaday for 6 weeks had no effect on erythrocyte SOD or serum Cp protein concentration in healthy adults (12 males and 12 females, aged 22 ± 46 y; Baker et al, 1999b). On the other hand, in depletion ± repletion type studies of women, in which SOD activity declined during Cu deprivation, recoveries of SOD activity were documented when either 3 mg (Reiser et al, 1985) or 4.3 ± 6.4 mg Cuaday were fed for more than 30 days (Kelvay et al, 1984;Miline et al, 1990), but not when less than 2.6 mg Cuaday was fed for periods of up to 42 day (Milne et al, 1988;Milne & Nielsen, 1996). This is consistent with the ®ndings of the present study, which showed that SOD activity increased after supplementation with 3 and 6 mg Cuaday for 28 days.…”
Section: Dietary Cu Supplementation and Bone Biomarkersmentioning
confidence: 99%
“…For example, we have recently shown in another double-blind, placebo-controlled crossover trial that Cu supplementation with 3 or 6 mg elemental Cuaday for 6 weeks had no effect on erythrocyte SOD or serum Cp protein concentration in healthy adults (12 males and 12 females, aged 22 ± 46 y; Baker et al, 1999b). On the other hand, in depletion ± repletion type studies of women, in which SOD activity declined during Cu deprivation, recoveries of SOD activity were documented when either 3 mg (Reiser et al, 1985) or 4.3 ± 6.4 mg Cuaday were fed for more than 30 days (Kelvay et al, 1984;Miline et al, 1990), but not when less than 2.6 mg Cuaday was fed for periods of up to 42 day (Milne et al, 1988;Milne & Nielsen, 1996). This is consistent with the ®ndings of the present study, which showed that SOD activity increased after supplementation with 3 and 6 mg Cuaday for 28 days.…”
Section: Dietary Cu Supplementation and Bone Biomarkersmentioning
confidence: 99%
“…Fructose has indeed been reported to decrease copper absorption in rats [14]. A diet containing up to 20% energy as fructose had however no adverse effect on copper balance in humans [15]. Fructose also increases iron absorption in rats [15] but does not appear to alter zinc bioavailability [16].…”
Section: Introductionmentioning
confidence: 99%
“…A diet containing up to 20% energy as fructose had however no adverse effect on copper balance in humans [15]. Fructose also increases iron absorption in rats [15] but does not appear to alter zinc bioavailability [16]. The effects of fructose on calcium metabolism have also been documented.…”
mentioning
confidence: 99%
“…(3) After dietary Cu depletion (0.79 mg Cu=day for 24 h) and subsequent Cu repletion (7.53 mg Cu=day for 42 and 24 days), no changes in plasma Cu and ceruloplasmin concentrations or in erythrocyte's SOD activity were observed (Turnlund et al, 1990). (4) After reduced Cu intake for 77 days (1.03 mg=day 2850 kcal with 20% fructose), the plasma concentrations of Cu and ceruloplasmin were unchanged, while erythrocyte's SOD activity decreased and increased again after repletion (3 mg Cu=day for 21 days, Reiser et al, 1985). The serum-Cu concentration is homeostatically regulated.…”
Section: How Is Cu Homeostasis Maintained?mentioning
confidence: 99%